Macrophage and Fibroblast Interactions in Biomaterial‐Mediated Fibrosis - Witherel, Claire E.; Abebayehu, Daniel; Barker, Thomas H.; Spiller, Kara L. (Advanced healthcare materials, 2019)
Biomaterial‐mediated inflammation and fibrosis remain a prominent challenge in designing materials to support tissue repair and regeneration. Despite the many biomaterial technologies that have been designed to evade or suppress inflammation (i.e., delivery of anti‐inflammatory drugs, hydrophobic coatings, etc.), many materials are still subject to a foreign body response, resulting in encapsulation of dense, scar‐like extracellular matrix. The primary cells involved in biomaterial‐mediated fibrosis are macrophages, which modulate inflammation, and fibroblasts, which primarily lay down new extracellular matrix. While macrophages and fibroblasts are implicated in driving biomaterial‐mediated fibrosis, the signaling pathways and spatiotemporal crosstalk between these cell types remain loosely defined. In this review, the role of M1 and M2 macrophages (and soluble cues) involved in the fibrous encapsulation of biomaterials in vivo is investigated, with additional focus on fibroblast and macrophage crosstalk in vitro along with in vitro models to study the foreign body response. Lastly, several strategies that have been used to specifically modulate macrophage and fibroblast behavior in vitro and in vivo to control biomaterial‐mediated fibrosis are highlighted. Macrophages and fibroblasts play major roles in biomaterial‐mediated and pathological fibrosis, but their distinct phenotypes and subsequent crosstalk remain loosely defined. This review discusses the role of macrophage phenotypes in fibrosis in vivo, in vitro models to study biomaterial‐mediated fibrosis, macrophage and fibroblast crosstalk in vitro, along with biomaterial strategies to modulate macrophage and fibroblast behavior for tissue regeneration.